TINJAUAN YURIDIS ATAS KEWAJIBAN NOTARIS DALAM MEMBACAKAN AKTA NOTARIS DAN IMPLIKASI HUKUMNYA (Studi Putusan Mahkamah Agung No. 351 PK/Pdt/2018) - Adela Destaliya; Mohamad Fajri Mekka Putra (The Juris, 2022)
This journal discusses the juridical review of the obligation of a notary to read a notarial deed and the legal implications of not reading a notary deed, based on Supreme Court Decision No. 351 PK/Pdt 2018, which in this review decision, the Panel of Judges annul: (i) Decision on cassation (Supreme Court Decision Number 560 K/Pdt/2016); (ii) Decision on appeal (Decision of the Bandung High Court with Decision Number 477/PDT.2014.PT.Bdg); and (iii) the decision of the Cibadak District Court (by Decision Number 27/Pdt.G/2013/PN Cbd.,). In the High Court's decision, the Sale and Purchase Binding Deed Number 12 made before Notary DS dated June 25, 2010 was canceled with the consideration that Notary DS as the defendant did not read the deed to the plaintiff, namely Sunardi's heirs, in this case the seller and owner of the land object. and delaying for more than 3 (three) years not providing a copy of the deed to the seller and then canceling the deed of sale and purchase agreement binding agreement between Sunardi's heirs and PT Sinar Timur Industrindo. However, in the review decision, the Panel of Judges considered that there was an error from the Judge to cancel the deed of sale and purchase agreement without involving one of the parties making the agreement (PT Sinar Timur Astrindo) in the lawsuit because in the decision there were only Sunardi heirs as the land owner (in the case as the seller) and PT Sinar Timur Industrindo (in the case as the buyer) were not involved and became parties to the lawsuit. The panel of judges considered that this violated the principles of contract law.